The role and importance of the institution of mediation in the mechanism of alternative dispute resolution (Texas Journal of Multidisciplinary Studies, 2022)
The article considers with the emergence of legislative foundations of mediation, meaning of the concept, history of formation, essence, principles, stages and classification issues.